CLINICAL COURSE AND DIAGNOSTICS OF NON-PSYCHOTIC AFFECTIVE DISORDERS BASED ON LONG-TERM CATAMNESIS - V. S. Sobennikov; V. V. Sobennikova; E. V. Vinokurov (Acta Biomedica Scientifica)
Individual variation in the clinical trajectories of affective disorder may have prognostic and therapeutic implications. We aimed to describe the long-term clinical course and outcome of non-psychotic affective disorder based on 5-year catamnesis. Medical records of 47 patients were studied (12 men, 35 women). The studied cases are characterized by polymorphism of symptoms and high levels of somatization and comorbid disorders. At first hospitalization only 46,8 % of cases diagnosed matched category F3 (ICD-10), a high level of double diagnosis has been described (14 cases - 29,8 %). Subsequent hospitalizations increased frequency of diagnosis of bipolar disorder type 2 (DSM-IV) - from 6,4 % to 33,3 % (p < 0,005). The problem of early recognition of non-psychotic affective disorders was discussed.